2014 IEEE Globecom Workshops (GC Wkshps) 2014
DOI: 10.1109/glocomw.2014.7063624
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocity enhancement and decorrelation schemes for PHY-based key generation

Abstract: Providing secure communication links between devices of low computational power has been increasingly investigated during recent years. The need for fast and easy-to-implement security for computationally weak wireless devices has lead to the development of physical layer based key generation approaches. The generation of symmetric cryptographic keys out of wireless channel properties turned out to be a promising approach comprising advantages of symmetric as well as asymmetric cryptography. Numerous quantizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The decorrelation algorithms themselves do not introduce more entropy but only aggregate the energy. In addition, the algorithms' complexities increase with the data block length [48], which may not be applicable to limited computational capacity devices. A rule of thumb for the optimal probing rate is thus attractive as it does not require any other additional signal processing.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The decorrelation algorithms themselves do not introduce more entropy but only aggregate the energy. In addition, the algorithms' complexities increase with the data block length [48], which may not be applicable to limited computational capacity devices. A rule of thumb for the optimal probing rate is thus attractive as it does not require any other additional signal processing.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Until now, there has existed unavoidable bit disagreements between Q A and Q B , caused by time delay in TDD systems, hardware differences, and noise [21]. Although some preprocessing approaches, e.g, principal component analysis (PCA) [20], are applied, the bit disagreements are not fully eliminated.…”
Section: Secret Key Generation Processmentioning
confidence: 99%
“…Chen et al [30] proposed an allocation mechanism to improve the SKGR for two-relays based cooperative MIMO architectures. Gopinath et al [31] analyzed various pre-processing techniques for PLS based key generation. The results of [31] showed that utilizing reciprocal properties of physical channel enhances the probability of agreement between the generated keys while de-correlation can mitigate key redundancy.…”
Section: A Related Workmentioning
confidence: 99%
“…Gopinath et al [31] analyzed various pre-processing techniques for PLS based key generation. The results of [31] showed that utilizing reciprocal properties of physical channel enhances the probability of agreement between the generated keys while de-correlation can mitigate key redundancy. Sadeghi et al [32] investigated the impact of in-band full-duplex wireless communications on SKG.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation